2012
DOI: 10.1242/jcs.091702
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autophagy in ESCRT mutants is an adaptive response for cell survival in C. elegans

Abstract: SummaryEndosomes and autophagosomes are two vesicular compartments involved in the degradation and recycling of cellular material. They both undergo a maturation process and finally fuse with the lysosome. In mammals, the convergence between endosomes and autophagosomes is a multistep process that can generate intermediate vesicles named amphisomes. Using knockdowns and mutants of the ESCRT machinery (ESCRT-0-ESCRT-III, ATPase VPS-4) and the autophagic pathway (LGG-1, LGG-2, ATG-7, TOR), we analyzed in vivo th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 60 publications
8
47
1
3
Order By: Relevance
“…Prior studies demonstrated that when autophagic reporters labeled with GFP are delivered to the vacuole, the GFP moiety is cleaved and accumulates in a free form due to its stability inside the vacuole (Djeddi et al, 2012;Li et al, 2014). In this way, the ratio of free GFP to GFP-tagged protein can be used as a semiquantitative measure of autophagic flux and whether this delivery changes with environmental or genetic perturbations.…”
Section: Impaired Autophagosome Formation and Autophagic Cargo Transpmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies demonstrated that when autophagic reporters labeled with GFP are delivered to the vacuole, the GFP moiety is cleaved and accumulates in a free form due to its stability inside the vacuole (Djeddi et al, 2012;Li et al, 2014). In this way, the ratio of free GFP to GFP-tagged protein can be used as a semiquantitative measure of autophagic flux and whether this delivery changes with environmental or genetic perturbations.…”
Section: Impaired Autophagosome Formation and Autophagic Cargo Transpmentioning
confidence: 99%
“…These phenomena, together with the presence of arrested phagophores and the reduced autophagy-mediated degradation of the plastid marker RECA-GFP, clearly point to a direct role for CHMP1 in plastid autophagy. Like the Arabidopsis chmp1 mutant, C. elegans ESCRT mutants (Djeddi et al, 2012) show increased autophagy as measured by GFP cleavage from the autophagic reporter GFP-ATG8. This observation led to the conclusion that the ESCRT machinery is not required for autophagosome maturation and that the accumulation of autophagosomes in ESCRT mutants is due to the upregulation of the autophagy pathway (Djeddi et al, 2012).…”
Section: A Mechanistic Connection Between Escrt Proteins and Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…New light has been thrown onto this situation through the discovery that ESCRT is also involved in autophagy. More and more studies on nematodes, flies, mammals, and even on plants provide evidence to support the conclusion that the inactivation of ESCRT machinery causes an accumulation of autophagosomes (9)(10)(11)(12)(13). Different models, such as the induction of autophagy or the disruption of autophagosome-endosome/lysosome fusion, have been proposed to explain the observation that autophagosomes accumulate in ESCRT-depleted cells (14,15).…”
mentioning
confidence: 97%